Clinical characteristics and prognosis of patients with multiple intracranial aneurysms living on the Tibetan Plateau of China - Dongliang Wang; Jiuqi Wuli; Xudong Cao; Bin Wang; Zeng Ren; Yu Weng; Kexue Wu (Journal of International Medical Research)
Objectives Although there is no consensus on the difference in rupture rates between multiple intracranial aneurysms (MIAs) and single intracranial aneurysms (SIAs), patients with MIAs may have poorer outcomes after rupture than patients with SIAs. In this study, we aimed to analyze differences in clinical characteristics between MIAs and SIAs and to evaluate the prognosis of patients with MIAs on the Tibetan Plateau who received different clinical treatments. Methods We retrospectively analyzed the clinical data of 68 patients with MIAs and 68 patients with SIAs admitted to Tibet Autonomous Region People’s Hospital. Univariate and multivariate analyses were used for data analysis. Results Compared with patients who had SIAs, those with MIAs were more likely to be female, smokers, alcohol drinkers, and hypertensive. The difference between the two groups in terms of size of the ruptured aneurysms was statistically significant. No significant differences in treatment effects were observed between patients with SIAs and those with MIAs at 3, 6, and 12 months. Conclusions Among patients living on the Tibetan Plateau, those with MIAs were more likely to be female, smokers, alcohol drinkers, and hypertensive. Endovascular treatment was superior to conservative management but not significantly better than craniotomy.